Pengaruh Inflasi dan Pertumbuhan Ekonomi Terhadap Jumlah Penduduk Miskin di Indonesia - Rasidin Karo Karo Sitepu; Diyah Puspa Asih Atsilanti; Marcella Magdhalena Erlely; Alsa Az Zukhruf; Muhammad Ifran; Salsa Nur Maulida; Abib Riyadi; Disya Ayu (Jurnal Akuntan Publik, 2025)
Indonesia, with its rapid economic growth, is still haunted by persistent poverty problems. Inflation is like a parasite that sticks to economic growth, has the potential to worsen the poverty gap and hinder its overcoming. The aim of this research is to examine how economic growth and inflation in Indonesia affect the level of poverty in Indonesia. Panel data collected between 1994 and 2023 from 34 provinces in Indonesia is the data source. Multiple linear regression analysis is the technique used. The findings show that the number of poor people in Indonesia is not significantly affected by economic growth or inflation. Only 25.7% of the fluctuation in the number of poor people can be explained by the regression model, based on a coefficient of determination (R-square) of 0.257; the remaining 74.3% can be explained by other factors not taken into account in this study.